2018
DOI: 10.1155/2018/7092414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stains on LDL Reduction and Liver Safety: A Systematic Review and Meta-Analysis

Abstract: Background and Aim Statin is a class of medications used to decrease low-density lipoprotein cholesterol level to prevent cardiovascular disease. However, the risk of hepatic damage caused by statin therapy is still controversial. We conducted a systematic review and meta-analysis summarizing the existing evidence of the effect of statin therapy on incidence of liver injury to clarify whether statin therapy could lead to liver function test abnormalities. Methods We searched the Cochrane Library, PubMed, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…Contrary to our and previous studies, a meta-analysis by Liang et al [33] suggested that statin use is associated with a significant increase in the risk of developing liver injury by 18%. However, there was no clear relationship between the dose or the lipid-lowering efficacy of different statins.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our and previous studies, a meta-analysis by Liang et al [33] suggested that statin use is associated with a significant increase in the risk of developing liver injury by 18%. However, there was no clear relationship between the dose or the lipid-lowering efficacy of different statins.…”
Section: Discussioncontrasting
confidence: 99%
“…Among subjects taking tolvaptan1statin, incidences of statin-related adverse events were not statistically different than those observed with placebo1statin. Statin use is associated with increased risk for musculoskeletal toxicity and liver enzyme elevations, and gastrointestinal symptoms are commonly reported (18)(19)(20). No significant increases in statin-related musculoskeletal events or gastrointestinal symptoms were seen in the tolvaptan1statin groups versus the placebo1statin groups across the TEMPO 3:4 and REPRISE studies, suggesting no increased risk of these adverse events in patients receiving tolvaptan and a statin.…”
Section: Discussionmentioning
confidence: 95%
“…A meta-analysis of twenty-one clinical trials also reported significant elevations in liver enzyme concentrations in all of these trials (p < 0.05) (43). Another meta-analysis highlighted an increased risk of liver injury in individuals using statins, particularly among those using fluvastatin (44).…”
Section: Discussionmentioning
confidence: 98%